2021
DOI: 10.1080/23311932.2020.1863620
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of harvesting stages and pre-storage treatments on shelf life and quality of tomato (Solanum lycopersicum L.)

Abstract: period and it increased the shelf life the fruits by about 10 days as compared to the control. From the results of the study, harvesting tomatoes at mature green stages and coating them with 50% cactus mucilage can be recommended for increasing the shelf life and quality of the tomato fruits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 32 publications
(50 reference statements)
6
14
0
Order By: Relevance
“…Similarly, immersing tomato fruits in 6% CaCl2 for 20 min before harvest maintained post-harvest quality by retarding lycopene content, weight loss, and microbial deterioration [39]. The current findings support those of Tolasa et al [40], who found that tomato fruits treated with CaCl2 had considerably lower lycopene concentration at room temperature.…”
Section: Antioxidant Properties Ascorbic Acid and Lycopenesupporting
confidence: 87%
“…Similarly, immersing tomato fruits in 6% CaCl2 for 20 min before harvest maintained post-harvest quality by retarding lycopene content, weight loss, and microbial deterioration [39]. The current findings support those of Tolasa et al [40], who found that tomato fruits treated with CaCl2 had considerably lower lycopene concentration at room temperature.…”
Section: Antioxidant Properties Ascorbic Acid and Lycopenesupporting
confidence: 87%
“…Another study showed that calmodulin is involved in the inhibition of ethylene biosynthesis due to the inactivation capability of the calcium-calmodulin complex in the ethylene biosynthesis pathway of tomato fruits [33]. Ethylene production was normally higher in green mature tomato fruits and the lower in higher doses of CaCl 2 initially and it was declined compared to the lower doses and control samples [11].…”
Section: Respiration Rate and Ethylene Productionmentioning
confidence: 99%
“…As a climacteric fruit, tomato can be harvested at different stages of maturity, for instance, green mature, breaker, turning, pink or light red, and red ripen stage [10]. These maturity stages significantly impact fruits' physiological process, postharvest performance, and sensory attributes after harvest [11]. Tomato fruits are harvested at inappropriate maturity stages, responsible mainly for the postharvest losses in developing countries [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In low-temperature disorders, sparked temporary accumulation of calcium ion is significant by various calcium capturing proteins, thus facilitating numerous physiological reactions in the cell (6). Calcium treatment is demonstrated to be effective on different kinds of fruits and vegetables such as chili pepper (7), loquat (8,9), apple (10), peach (11,12), persimmon (13), papaya (14,15), gooseberry (16), strawberry (17), mango (18), purple shallot (19), soursop (20), tomato (21) and watermelon (22). Banana (Musa spp.)…”
Section: Introductionmentioning
confidence: 99%